2001
DOI: 10.1177/14034948010290031201
|View full text |Cite
|
Sign up to set email alerts
|

Work ability and duration of certified sickness absence

Abstract: Work ability assessed by patients may be a useful prognostic indicator of duration in prolonged episodes of certified sickness absence. Further studies using other outcomes, such as disability pensioning, would be of interest to enlighten the concepts of work ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
37
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 22 publications
4
37
0
Order By: Relevance
“…We could only postulate that workers with more sickness absences (more than 60 d) may have developed coping strategies in order to maintain better selfestimated work ability compared to workers with less sickness absences (25 to 60 d). However, previous research has indicated that work ability is assessed lower for those with a longer duration of sickness absence compared to workers with less sickness absence 23) .…”
Section: Work Abilitymentioning
confidence: 85%
“…We could only postulate that workers with more sickness absences (more than 60 d) may have developed coping strategies in order to maintain better selfestimated work ability compared to workers with less sickness absences (25 to 60 d). However, previous research has indicated that work ability is assessed lower for those with a longer duration of sickness absence compared to workers with less sickness absence 23) .…”
Section: Work Abilitymentioning
confidence: 85%
“…Being a female increased the likelihood of return to work in two studies (8,21), while it decreased this likelihood in another study (10). Older age was predictive of not returning to work (10,13,(17)(18)(21)(22). Being divorced also decreased the likelihood of return to work (10).…”
mentioning
confidence: 98%
“…To our knowledge, no comprehensive review on factors that influence return to work among employees with common mental disorders has been published. Therefore, we reviewed the literature in search of disorder-related, personal, and environmental predictor variables that fulfilled our criterion of practical value in studies on either recovery from work disability among patients with common mental disorders (7)(8)(9) or duration of sickness absence in general (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…As LTSA precedes disability pension, it is conceivable that poor WAI scores also predict LTSA. Among sick-listed workers, poor WAI scores Schouten et al were found to be associated with a longer duration of LTSA (10,11). Only few studies related the WAI scores of non-sick-listed workers to their risk of future sickness absence.…”
mentioning
confidence: 99%